Non-destructive testing of metallic 3D printed specimens using velocity and attenuation measurements - Lim, Carina Kei Hui (2015)
As 3D printing is creating a storm in the technological world, everyone has hopped on to the bandwagon and giving this technology a shot. However, otherwise called additive manufacturing meant that it is still a process like no other thus the presence of defects is certain. The presence of defects may cause a potential life threatening situation should the part fails as 3D printed parts are replacing some of our everyday products. The consequence of a mechanical failure due to the presence of porosity is deadly. Therefore, this project aims to detect porosity in 3D printed specimens using non-destructive methods in the fastest yet most accurate way. The non-destructive methods to be compared are the use of ultrasound,computer tomography and eddy current. With their plus and minus points, ultrasound is the best method which is time saving and accurate as compared to the other two methods. However, all methods have the ability to categorize the specimens into low and high porosity content using a procedure called the red light procedure which is devised by ultrasound.